In situ immobilized, magnetite nanoplatelets over holey graphene nanoribbons for high performance solid state supercapacitor. (10th January 2017) - Lalwani, Shubra; Sahu, Vikrant; Marichi, Ram Bhagat; Singh, Gurmeet; Sharma, Raj Kishore
Graphical abstract: Highlights: Hexagonal platelet morphology of magnetite offers efficient material utilization. Enhanced electronic conductivity of Fe3 O4 /GNR nanocomposites via GNR-GNR network. Exploring the best optimized 30 wt. (%) Fe3 O4 on GNR as solid state supercapacitor. ABSTRACT: Among major phases of iron oxide, magnetite (Fe3 O4 ) is potential candidate for pseudocapacitors. Yet, the clustering of magnetite nanoparticles confines them from being exploited as charge storage material. Herein, magnetite hexagonal nanoplatelets are synthesized on holey graphene nanoribbons (GNRs) by hydrothermal route and tested for charge storage performance in solid-state supercapacitor incorporating gel electrolyte (PVA-H2 SO4 ). GNR besides providing large surface for adsorption of magnetite platelets also improved the charge collection ability of nanocomposite through interconnected nanoribbon network. Mass loading over GNR is optimized to a maximum of 30 wt. (%) by ensuring mono dispersion of magnetite nanoplatelets and high conductivity (14.0 S m −1 ) of nanocomposite. Above 50 wt. (%) magnetite loading, structural identity of nanoribbon is tempered and as a consequence increased network resistivity depletion in charge storage capacity is observed. Mass loading of magnetite over nanoribbon showed an inverse relationship with ion diffusion and electronic conduction. Balanced ionic and electronic conduction in 30 wt. (%) magnetite loaded nanoribbon results in a supercapacitor cell delivering 1241.5 W kg −1 while maintaining 26.9 Wh kg −1 energy density. About 95% capacitance retention over 3000 charge discharge cycles at 2.3 A g −1 demonstrate magnetite as a high performance supercapacitor electrode.